Ediciones críticas de comentarios bíblicos y tratados de astrología de Abraham ibn Ezra: problemas y dificultades - Gómez Aranda, Mariano (Henoch, 2023)
This article focuses on the critical editions of biblical commentaries and astrological works of Abraham ibn Ezra (Tudela, Spain 1089 - London, England ca. 1164). It analyses critically the different approaches used by the editors of Ibn Ezra’s works to fix the text by selecting the most correct readings from the manuscripts, basing on a comparison among the different manuscripts and on the history of transmission of the texts. Abraham ibn Ezra’s exegetical and scientific works had a remarkable impact in the Middle Ages, as they were copied, read, commented, and annotated several times. This fact constitutes a challenge to edit them critically. This article examines the most important problems for the editions of Ibn Ezra’s works, namely, the existence of more than one version of some his works, the combinations of versions in the codices, the modifications and additions introduced in his texts by readers, copyists, students or admirers, the role of his disciples in the transmission of some of Ibn Ezra’s comments and notes, the attribution to Ibn Ezra’s authorship of some complete biblical commentaries and scientific works, and the texts censored by Christian censors. Part of the article concentrates on the analysis of the specificities of the interventions of copyists, readers and disciples of Ibn Ezra in order to explain the reasons for their authorship and whether they can be attributed or not to the original author.